2016
DOI: 10.1523/jneurosci.3790-14.2016
|View full text |Cite
|
Sign up to set email alerts
|

Head Direction Cell Activity Is Absent in Mice without the Horizontal Semicircular Canals

Abstract: Head direction (HD) cells fire when an animal faces a particular direction in its environment, and they are thought to represent the neural correlate of the animal's perceived spatial orientation. Previous studies have shown that vestibular information is critical for generating the HD signal but have not delineated whether information from all three semicircular canals or just the horizontal canals, which are primarily sensitive to angular head rotation in the horizontal (yaw) plane, are critical for the sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 36 publications
2
41
0
Order By: Relevance
“…Vestibular inputs that generate the HD signal can be traced back to the contributions of individual vestibular sensory end organs. Recent experiments in transgenic mice have shown that the horizontal canals, which are mostly sensitive to angular acceleration in the yaw (horizontal) plane when the animal’s head is held in the upright position, are essential for generating the directional signal (Valerio and Taube, 2012). Yoder and Taube (2009) found that the otolith organs, which are sensitive to translational acceleration of the animal, are also known to play some role in the generation of the HD signal.…”
Section: The Hd Cell Network and Signal Generationmentioning
confidence: 99%
“…Vestibular inputs that generate the HD signal can be traced back to the contributions of individual vestibular sensory end organs. Recent experiments in transgenic mice have shown that the horizontal canals, which are mostly sensitive to angular acceleration in the yaw (horizontal) plane when the animal’s head is held in the upright position, are essential for generating the directional signal (Valerio and Taube, 2012). Yoder and Taube (2009) found that the otolith organs, which are sensitive to translational acceleration of the animal, are also known to play some role in the generation of the HD signal.…”
Section: The Hd Cell Network and Signal Generationmentioning
confidence: 99%
“…The vestibular system comprises the semicircular canals which detect angular head acceleration in three planes, and the otolith organs which detect linear head acceleration and static head position relative to gravity. Disruption of semicircular canal function eliminates the directional tuning of head direction cells and often causes the animal to spin or circle within a limited area [20, 21]. The otolith organs also contribute to head direction cell function, but this contribution appears to be relatively less than that of the canals; otoconia-deficient mice have head direction cells that are directionally tuned, but this tuning degrades over time [22].…”
Section: Introductionmentioning
confidence: 99%
“…Vestibular inputs make a decisive contribution to head directional firing of neurons in the anterodorsal nucleus of the thalamus 1,7,8 and lesions of this thalamic region abolish head direction firing in presubiculum 6 . Head direction signals transmitted via the thalamus are integrated in the presubiculum with visual information 5 from visual 9 and retrosplenial cortices 7 , and information from the hippocampal formation 2 .…”
Section: Introductionmentioning
confidence: 99%